Subclinical Thyrotoxicosis and Cardiovascular Risk: Assessment of Circulating Endothelial Progenitor Cells, Proangiogenic Cells, and Endothelial Function - Phowira, Jason; Bakhashab, Sherin; Doddaballapur, Anuradha; Weaver, Jolanta U. (Frontiers in Endocrinology, 2022)
Background Subclinical thyrotoxicosis (SCT) is defined by low or undetectable thyroid-stimulating hormones and normal thyroid hormones. The treatment of SCT is uncertain despite being associated with increased cardiovascular risk (CVR) and mortality. Circulating endothelial progenitor cells (cEPCs) and circulating angiogenic cells (CACs) have been found to be reduced in conditions with CVR. We aimed to evaluate whether endothelial function and cEPC and CAC counts were reduced in SCT and to study the in vitro effect of triiodothyronine (T3) on proangiogenic cell (PAC) function from young healthy controls. Methods cEPCs (quantified by flow cytometry, 20 SCT/20 controls), CACs following in vitro cultures (15 SCT/14 controls), paracrine function of CACs, endothelial function by flow-mediated dilation (FMD, 9 SCT/9 controls), and the effect of T3 on apoptosis and endothelial nitric oxide synthase (eNOS) expression in PACs were studied. Results p < 0.001, CD133+/VEGFR-2+ 0.4 (0.0–0.7) vs. 0.6 (0.0–4.6), p = 0.009, CD34+/VEGFR-2+ 0.3 (0.0–1.0) vs. 0.7 (0.1–4.9), p = 0.002; while CAC count was similar. SCT predicted a lower cEPC count after adjustment for conventional CVR factors. FMD was lower in SCT subjects versus controls (% mean ± SD, 2.7 ± 2.3 vs. 6.1 ± 2.3, p = 0.005). In vitro studies showed T3 increased early apoptosis and reduced eNOS expression in PACs. Conclusions In conclusion, SCT is associated with reduced cEPC count and FMD, confirming increased CVR in SCT. Future outcome trials are required to examine if treatment of this subclinical hyperactive state improves cardiovascular outcome. Clinical Trial Registration http://www.controlled-trials.com/isrctn/, identifier ISRCTN70334066.